Türkistan’da İslâm dininin Anlaşılmasında Ahmed Yesevî ve Dil - KANABAEV, Zhamalidin (Scientific Journal of Faculty of Theology, 2017)
Ahmet Yesevi is one of the most important figures in the spreading and understanding of Islam in Turkestan. He enchanted Islam with the language of poetry. He described Islam with the language used by the people in that region and interprets without ignoring the customs and cultures of the nomadic Turkic tribes.